Perbandingan Return Investasi Surat Berharga Negara Ritel dan Return Investasi Saham IDX30 di Masa Pandemi - Hanif Noer Rofiq (J-MAS (Jurnal Manajemen dan Sains), 2022)
Investment is one way to keep our money so that it is not intrinsically reduced due to inflation. Many investment instruments range from gold, stocks, cryptocurrencies, and state securities. The current COVID-19 pandemic is an excellent opportunity to see which investment instruments can give a better return amid global economic uncertainty. In choosing investments, investors should not fear and follow the bias generated by other investors during the pandemic. Thus, this research was conducted to determine objectively which investment provides the highest return during the pandemic, between the low-risk investments represented by gold and SBN; and high-risk investments represented by IDX30. The results of this study indicate that within two years of the pandemic in Indonesia, IDX30 stock returns were higher than gold and SBN returns. This is in line with the concept of high-risk high return, where the risk of the stock is higher than the risk of the other two types of investments analyzed.